Money after Blockchain: Gold, Decentralised Politics and the New Libertarianism. - Allon, Fiona (Australian Feminist Studies, 2018)
Blockchain technologies are central to what has been described as a new ‘smart social contract’. With blockchain, individual cryptographic identity becomes the basis for new forms of money and for a whole suite of restructured social, political and financial transactions. But what do these developments signal for feminist engagements with the money economy? The transparency and pseudonymity that the blockchain provides has been welcomed as a ‘feminist weapon’. But the decentralised technology also legitimises many longstanding assumptions of libertarianism, especially competitive individualism, naturalised social inequality and the stability of value associated with the gold standard. Drawing on popular culture texts, Goldfinger and The Mandibles, this article considers this history, examining the gendered, racialised and sexualised discursive practices that attend representations of gold along with the ‘metallism’ surrounding blockchain-based cryptocurrencies in the contemporary conjuncture. By claiming to represent non-negotiable certainty derived from technology/nature rather than social convention, the fantasy of fundamental value returns, together with related associations of essentialism and authenticity, but anchored in this new context in the technocratic authoritarianism of FinTech. This is part of the background for the ‘new libertarianism’ whose ascendency now overshadows the neoliberalism that has been the focus of critical attention for some decades.